2018
DOI: 10.1002/aenm.201803024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Dipole Moment Cation on Layered 2D Organic–Inorganic Halide Perovskite Solar Cells

Abstract: Layered 2D organic–inorganic hybrid perovskite is appearing as a rising star in the photovoltaic field, thanks to its superior moisture resistance by the organic spacer cations. Unfortunately, these cations lead to high exciton binding energy in the 2D perovskites, which suffers from lower efficiency in the devices. It thus requires a clear criterion to select/design appropriate organic spacer cations to improve the device efficiency based on this class of materials. Here, 2,2,2‐trifluoroethylamine (F3EA+) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 62 publications
1
112
0
Order By: Relevance
“…The slopes for BA ( n = 4) and Gly ( n = 4) perovskite devices are 1.68 and 1.42 kT / q , respectively ( k is Boltzmann's constant, T is temperature, and q is elementary charge), indicating that trap‐assisted recombination existed in the devices. [ 45–47 ] In comparison with that of BA ( n = 4) device, the slope of Gly ( n = 4) perovskite device is smaller and closer to 1 kT / q , which suggest lower trap‐assisted recombination. Therefore, low‐dimensional RP devices based on Gly ( n = 4) have higher V oc and thus higher PCE.…”
Section: Resultsmentioning
confidence: 99%
“…The slopes for BA ( n = 4) and Gly ( n = 4) perovskite devices are 1.68 and 1.42 kT / q , respectively ( k is Boltzmann's constant, T is temperature, and q is elementary charge), indicating that trap‐assisted recombination existed in the devices. [ 45–47 ] In comparison with that of BA ( n = 4) device, the slope of Gly ( n = 4) perovskite device is smaller and closer to 1 kT / q , which suggest lower trap‐assisted recombination. Therefore, low‐dimensional RP devices based on Gly ( n = 4) have higher V oc and thus higher PCE.…”
Section: Resultsmentioning
confidence: 99%
“…2D perovskite structure generally has a formula (L) 2 A n −1 M n X 3 n + 1 , where L stands for ligands with long carbon chain molecules with one amino group, A is usually methylammonium (MA + ) or formamidinium (FA + ) ions, M is usually Pb or Sn, X is typically halide, such as iodide, bromide, and chloride. But to date, the insulating ligands, i.e., BA ( n ‐butylammonium) and PEA (phenethylammonium), are mostly investigated by researchers to form Ruddelsden–Popper (RP) phase 2D perovskites . RP phase 2D perovskites are attractive for several reasons: First, the solution‐processed 2D perovskite film exhibits the unique multicomponent quantum wells (MQW) structure that could naturally confine excitons, showing their enormous potential in light emitting diode (LED) applications .…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, several pioneering works fabricated novel RPPs based on binary spacer (PEA‐BA, BA‐GA [guanidinium], BA‐F 3 EA [trifluoroethylamine], and BA‐PEA), and found that the introduction of binary spacer led to the preferable crystal growth, more efficient charge transport, and better device performance. However, the above studies paid more attention to the assistant effect of a second spacer on the crystallization dynamics and charge transport of RPP films based on the main spacer, and the second spacer just had a low molar concentration of 0–30% . Due to the compositional complexity and the consequent fabrication difficulty of high‐quality films, it still lacks the profound understanding of the interplay of binary spacer in the overall mixture range of 0–100% in RPPs until now, and their effects on the precursor chemistry, film quality, and carrier behavior need to be urgently explored.…”
Section: Introductionmentioning
confidence: 99%